MODIFIKASI ZEOLIT ALAM SEBAGAI ADSORBEN AMMONIUM HIDROKSIDA (NH4OH) - Nur Indah Fajar Mukti (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Natural zeolite is a mineral that are widely available in Indonesia. Among many other benefits, the natural zeolite can be used as an adsorbent to reduce water pollutant caused by ammonia compounds and combination of derivatives. This research aimed to study the effect of natural zeolite dealumination on the adsorption properties of ammonium hydroxide (NH4OH). Dealumination effect was studied by varying the concentration of HNO3 (0.5 N, 5 N and 10 N). The adsorption process of NH4OH was observed by studying the adsorption time with amount of NH4OH adsorbed on the surface of the zeolite. In addition, also studied the effect of heating (calcination) after dealumination to the NH4OH uptake. In this study, NH4OH adsorbed on zeolite surface was observed by Fourier Transform Infrared (FTIR). Results were showed that the amount of NH4OH adsorbed on H- zeolite has a maximum (80.8%) at 5 N HNO3. From the calcination process, it was noted that H-zeolite undergo calcination process has higher NH4OH adsorption capacity than that of the H-zeolite without a calcination process. FTIR analysis was showed that NH4OH adsorbed on the surface of H- zeolite on BrÃ¸nsted acid peak.